Did COVID-19–Era Tax Incentives Coincide with Changes in Corporate Tax Avoidance? Evidence from Indonesia (2019–2020) - Dian Indriana Hapsari; Juli Ratnawati (Pusat Riset dan Inovasi Nasional, 2026)
Indonesia still faces serious challenges related to the low tax ratio due to tax avoidance practices. In 2020, the value of corporate tax avoidance was recorded at Rp 67.6 trillion. This study aims to test whether there is a significant difference between tax avoidance practices before the pandemic (2019) and during the pandemic (2020). The research method uses a quantitative approach with purposive sampling techniques. Data is obtained from the company's financial statements listed on the Indonesia Stock Exchange (IDX). The study population consisted of 206 companies, with 91 companies meeting the criteria as samples. Data analysis was carried out using a paired sample t-test with tax avoidance variables in 2019 and 2020. The results of the study show that there are significant differences in tax avoidance practices before and during the pandemic. These findings indicate that the crisis conditions caused by the COVID-19 pandemic are affecting companies' strategies in managing tax liabilities, including the tendency to increase tax avoidance practices. This research contributes to the development of fiscal policy by emphasizing the importance of stricter supervision and regulation to minimize tax avoidance practices, especially in economic crisis situations.